Security Protocols XXI 21st International Workshop, Cambridge, UK, March 19-20, 2013, Revised Selected Papers - Christianson, Bruce.; Malcolm, James.; Stajano, Frank.; Anderson, Jonathan.; Bonneau, Joseph. (Lecture Notes in Computer Science, 2013)
This book constitutes the thoroughly refereed post-workshop proceedings of the 21st International Workshop on Security Protocols, held in Cambridge, UK, in March 2013. The volume contains 14 revised papers with transcripts of the presentation and workshop discussion and an introduction, i.e. 15 contributions in total. The theme of the workshop was "What's Happening on the Other Channel?".